Dose-response evaluation of a copaiba-containing varnish against streptococcus mutans in vivo - Valadas, Lídia Audrey Rocha (2019)
Introduction: Dental caries is the most prevalent disease in humans and its incidence is particularly high during childhood. The use of medicinal plants is a common practice in Brazil. Objective: To evaluate the optimal antimicrobial concentration of Copaifera langsdorffii (copaiba) oil-resin, in the form of dental varnish, against Streptococcus mutans (S. mutans) in children. Methods: Twenty-four children, caries-free, aged until 6 years old, were selected to participate in this study. The varnish was applied to the occlusal surfaces of all deciduous molars. The antimicrobial activity was analyzed in saliva, whose collection was conducted in two phases: before applying the copaiba varnish and after use to verify the instantaneous effectiveness of Copaifera langsdorffii dental varnish in the reduction of S. mutans. The microbiological analysis was repeated twice, establishing dilutions of 1:10 mL and 1:100 mL. Results: Comparisons between different times within the same dilution were carried out by repeated measures analysis of variance (ANOVA) associated with Tukey’s multiple comparisons test. Comparisons of conditions prior to and after treatment were performed using the t test for paired samples and it indicated that the 1% formulation promoted a more significant decrease in the number of S. mutans colonies (p = 0,0026). Conclusion: Copaiba oil-resin, in the form of dental varnish, has antimicrobial activity against S. mutans in all the concentrations studied. Further studies to identify the long-term activity and anticaries effect of this varnish are required to establish its use in caries prevention.